Impact of vacuum frying on quality of potato crisps and frying oil. (15th February 2018) - Belkova, Beverly; Hradecky, Jaromir; Hurkova, Kamila; Forstova, Veronika; Vaclavik, Lukas; Hajslova, Jana
Highlights: Vacuum frying reduced acrylamide content in potato crisps by 98%. Vacuum fried crisps have better nutritional parameters. Vacuum frying lowered the extent of heat-induced changes in the frying oil. DART-MS enabled good differentiation of vacuum and conventional frying oil. Abstract: This research was focused on a critical assessment of vacuum frying as a technology enabling minimization of acrylamide formation in potato crisps and reducing undesirable chemical changes that occur in frying oil at high temperatures. The potato slices were fried in rapeseed oil under vacuum at 125 °C and atmospheric pressure at 165 °C. The experiments were performed on two potato varieties, Saturna and Impala. Vacuum frying reduced the formation of acrylamide by 98% and also other Maillard reaction products, specifically alkylpyrazines. Concurrently a lower extent of oxidative changes was observed in the frying oil, while 3-MCPD esters decreased fairly quickly during conventional frying. Sensory characteristics of the vacuum and conventionally fried potato crisps were evaluated by a 23-member panel. The majority of panellists preferred the flavour of 'conventional crisps', while only a few of them appreciated potato-like fresh flavour of 'vacuum crisps' and classified this product as 'tasty'.